Estimation of load reduction factors for clay masonry walls. - Da Porto, Francesca (Earthquake engineering & structural dynamics.)
The in-plane cyclic behaviour of three types of unreinforced clay masonry was characterized by means of laboratory tests on full-scale specimens. The masonry walls were assembled with various bonding arrangements (head joints made with mortar pockets, dry head joints with mechanical interlocking, thin-layer mortar bed joints), which are not yet inserted in seismic codes. Experimental behaviour was modelled with an analytical hysteretic model able to predict lateral load?displacement curves in case of shear failure of the unreinforced walls. According to the experimental results and those of the selected analytical model, parametric study to evaluate the reduction in lateral strength demand produced by non-linear behaviour in masonry walls, i.e. the load reduction factor was carried out by non-linear dynamic analyses. The calculated values of the load reduction factor were modest. The differences in values found for the three masonry types, although consistent with them, were not great. This may indicate that, in the ultimate limit state, the type of masonry cannot significantly affect the behaviour of an entire building.